From risk to reward: Japan's potential for health and economic improvements - Eiko Saito; Federico Podestà (Springer, 2024)
Abstract This study examines the relationship between risky consumption behaviors, non-communicable diseases (NCDs), and socioeconomic costs in Japan using the Preventable Risk Integrated ModEl (PRIME). We assess the potential impact of healthier lifestyle choices on NCD incidences and costs in 2019. Japan's rising healthcare expenditures threaten its economic future. Excessive intake of salt, tobacco, and alcohol, along with insufficient fiber and fruit consumption, significantly contribute to high NCD rates. Our analysis shows that healthier behaviors could have prevented 564,000 NCD cases, potentially saving $35 billion in health costs and economic losses in 2019. We consider scenarios where smokers switch to heated tobacco products (HTPs), applying conservative risk reduction estimates. Higher risk reduction levels could triple smoking-attributable savings. Projecting these savings over ten years would increase economic benefits tenfold. The study emphasizes the need for comprehensive public health strategies promoting healthier lifestyles. Targeted interventions, such as stricter regulation of high-risk products and incentives for healthier alternatives, could reduce NCD incidences and healthcare costs. While PRIME provides valuable insights, further research is needed to refine our understanding of risk factor-disease relationships.